Deformation Analysis of Bromo Mountain Caused by Eruption Activity in December 2015-February 2016 Using Differential Interferometry Synthetic Aperture Radar (DInSAR) - Imelda Vinny Aprillisa; Muhammad Taufik; Ira Mutiara Anjasmara (IPTEK Journal of Proceedings Series, 2019)
Bromo mountain is one of the most active volcanoes in East Java. In December 2015 - January 2016 the Center for Volcanology and Geological Hazard Mitigation detected increased activities on Bromo mountain. The existence of volcanic activities cause a deformations on the surface of Bromo mountain. The existing deformations on the surface of Mount Bromo can be measured with various technologies such as using DInSAR. In this study, the analysis of deformation on the surface of Mount Bromo are done by DInSAR processing using two-pass method and using five Sentinel-1A satellite imagery in November 2015, December 2015, January 2016, February 2016, and March 2016 and DEM SRTM 30 meters. The results show that the two-pass method of DInSAR can reflect the increased activities in Bromo mountain that cause the deformation of the surface where the majority of deformations occur at the caldera of Bromo mountain. From this method, the result of LOS (Line of Sight) displacement value indicates that the maximum subsidence occured in December 2015 - January 2016 with the value -20 mm s / d -60 mm it indicates if there were some increased activities on the crater of Bromo mountain in December 2015 to January 2016. While the maximum uplift occurred in February 2016 - March 2016 with the value 0 mm s / d 40 mm it indicates if the activities on the crater of Bromo mountain was decreasing. However, in order validate the accurate value of deformation, it is necessary to compare with other measurements or measuring directly in the field